2014
DOI: 10.1093/mnras/stu682
|View full text |Cite
|
Sign up to set email alerts
|

Variability of the giant X-ray bump in GRB 121027A and its possible origin

Abstract: The particular giant X-ray bump of GRB 121027A triggered by Swift is quite different from the typical X-ray flares in gamma-ray bursts. There exhibit four parts of the observed structural variabilities in the rise and decay phase of the bump. Considering the quality of four parts of the data, we can only analyze the data from about 5300 s to about 6100 s in the bump using the stepwise filter correlation method (Gao et al. 2012), and find that the 86 +5.9 −9.4 s periodic oscillation may exist, which is confirme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Pruet et al (2004a) adopted a steady-state wind model to simulate the outflow and found that the electron fractions depend on the viscosity and accretion rate of the disk. Most recently, the detailed properties of the jet or outflow ejected by the system of accretion disk and black hole have been improved by many works (Hou et al 2014;Liu et al 2010;Reynoso et al 2006, etc. ), which can explain the shapes of observed profiles for a wide variety of GRBs.…”
Section: Discussionmentioning
confidence: 99%
“…Pruet et al (2004a) adopted a steady-state wind model to simulate the outflow and found that the electron fractions depend on the viscosity and accretion rate of the disk. Most recently, the detailed properties of the jet or outflow ejected by the system of accretion disk and black hole have been improved by many works (Hou et al 2014;Liu et al 2010;Reynoso et al 2006, etc. ), which can explain the shapes of observed profiles for a wide variety of GRBs.…”
Section: Discussionmentioning
confidence: 99%
“…These types of massive stars (M ≥ 100 M ), which are thought to form in the early Universe at low metallicity (Z ∼ 10 −4 Z ), have also been proposed as progenitor of the so-called ultra-long GRBs (Salvaterra et al 2013;Ma et al 2015), i.e. GRB 111209A (Gendre et al 2013), GRB 121027A (Hou et al 2014), and GRB 130925A (Evans et al 2014).…”
Section: Pop III or Enriched Pop Ii Progenitormentioning
confidence: 99%
“…Observations with the Swift and Fermi satellites show that following the steep decline, many GRBs exhibit flares (e.g., Burrows et al 2005;Zhang et al 2006;Chincarini et al 2007;Falcone et al 2007;Yi et al 2016, giant bumps (e.g., Wu, Hou & Lei 2013;Hou et al 2014) or plateaus (e.g., Troja et al 2007;Liang, Zhang & Zhang 2007;Corsi & Mészáros 2009;Rowlinson et al 2013) in their X-ray light curves. These phenomena are closely related to the late-time activities of the GRB central engines (e.g., Bernardini et al 2011;Liu, Gu & Zhang 2017;Liu 2018Liu , 2019.…”
Section: Conclusion and Discussionmentioning
confidence: 99%